Penentuan Harga Opsi dengan Model Black-Scholes Menggunakan Metode Beda Hingga Center Time Center Space (CTCS) - Welgi Okta Irawan; Media Rosha; Dony Permana (UNIVERSITAS NEGERI PADANG, 2019)
Abstract – Stock options is defined as a contract between two parties that the person who buy the contract have the right to buy or sell some stocks at a price and a certain period. To generate the profit, investor have to calculate the fear price from the options how the options price can be bought or sold. The Black-Scholes Model is one of model for calculating the option price. By a method of finite difference CTCS, investor can calculate option price which previously formed in the Black-Scholes Model. This research aims to establish the option pricing formula with Black-Scholes Models using finite difference methods CTCS and apply it. For the example, it is determined the option price Apple (AAPL) stocks from the American stock exchange (NASDAQ). It is obtained bought option price and sold option price at 28 July 2017 are 5.2558 and 0.9734. The price of bought option in the market is 5.67 (>5.2558), so investor have to sell bought option. The price of sold option in the market is 1.32 (>0.9734), so investor have to sell sold option. Keywords – Stock Option, Black-Sholes Model, Finite Difference Method, CTCS